2021
DOI: 10.1111/ijcs.12698
|View full text |Cite
|
Sign up to set email alerts
|

Crisis‐induced behavior: From fear and frugality to the familiar

Abstract: This research uncovers the impact of a multifaceted crisis on consumers' immediate shopping behaviors, short‐term financial spending, and long‐term shopping and spending responses. This longitudinal study adopts a future studies approach to expose consumers' current experiences, expectations of the future, and realized future experiences to understand a pandemic's impact on consumers' collective shopping and spending behaviors. Data were collected at the beginning of the COVID‐19 pandemic, during its peak, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 73 publications
3
86
0
Order By: Relevance
“…Recently, adaptations in consumers' buying behaviour due to COVID‐19 have been studied under various themes (Kansiime et al., 2021 ; Laato et al., 2020 ; Pakravan‐Charvadeh et al., 2021 ; Pantano et al., 2020 ; Rayburn et al., 2021 ). Gordon‐Wilson ( 2021 ) noted that external influences such as COVID‐19 affected ‘consumer's feelings for self‐control’ by changing their shopping behaviour, type of shopping and preference of store format, and consumption of unhealthy snacks and alcohol.…”
Section: Background Literaturementioning
confidence: 99%
“…Recently, adaptations in consumers' buying behaviour due to COVID‐19 have been studied under various themes (Kansiime et al., 2021 ; Laato et al., 2020 ; Pakravan‐Charvadeh et al., 2021 ; Pantano et al., 2020 ; Rayburn et al., 2021 ). Gordon‐Wilson ( 2021 ) noted that external influences such as COVID‐19 affected ‘consumer's feelings for self‐control’ by changing their shopping behaviour, type of shopping and preference of store format, and consumption of unhealthy snacks and alcohol.…”
Section: Background Literaturementioning
confidence: 99%
“…For example, consumers are increasingly supporting local businesses and products (Kim et al, 2021), while also exhibiting an increased price consciousness (Kitz et al, 2021). While some consumers maintain crisis‐induced behaviours others return to familiar consumption behaviours (Rayburn et al, 2021; see also Gordon‐Wilson, 2021). At the same time, COVID‐19 has sharply increased consumer adoption of digital and contactless shopping (Kim & Im, 2021; Tran, 2021)—highlighting the importance of studying consumer behaviour in e‐commerce and emphasizing the role of technology‐mediated consumption as a coping strategy amidst such a crisis (Yap et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely not panic buying is not visible to others, so it is likely that its prevalence is exaggerated. Studies have shown that scarcity predicted increased panic buying during the COVID-19 pandemic, and the previous SARS pandemic (Chan and Koh, 2006;Rayburn et al, 2021). Regret is a more powerful motivator than positive emotions (Kahneman and Tversky, 1982), so purchases may be made to avoid the prospect of future regret of missing out.…”
Section: Theoretical Explanations For Panic Buyingmentioning
confidence: 99%